Comparative Study Between the Efficacy of Fractional CO2 Laser/Radiofrequency, PRP and a Combination of Both in the Treatment of Striae Distensae: A Pilot Study - Sany I; Mohamed Sobhi R; Badawi A; Mohamed Elmaadawi Z; Mostafa PIN (Dove Medical Press, 2022)
Iman Sany,1 Rehab Mohamed Sobhi,1 Ashraf Badawi,2,3 Zeinab Mohamed Elmaadawi,4 Pakinam Ibrahim Nabil Mostafa1 1Department of Dermatology, Kasr Alainy Medical School, Cairo University, Cairo, Egypt; 2Department of Medical Laser Applications, National Institute of Laser Enhanced Sciences, Cairo University, Cairo, Egypt; 3Department of Dermatology, Faculty of Medicine, University of Szeged, Szeged, Hungary; 4Department of Histology & Cell Biology, Kasr Alainy Medical School, Cairo University, Cairo, EgyptCorrespondence: Pakinam Ibrahim Nabil Mostafa, Lecturer of Dermatology, Kasr Alainy Medical School, Cairo University, PO Box 11519, 4 Gemey St, Garden City, Cairo, Egypt, Tel +201002576451, Email pakinamnabil@kasralainy.edu.egPurpose: The work aims to compare the effect of platelet-rich plasma versus fractional CO22 laser/radiofrequency versus both methods combined in treating striae distensae.Patients & Methods: The study included ten female patients with striae alba with Fitzpatrick IV skin. Three sites of striae were chosen; one was treated with platelet-rich plasma, another with fractional CO2 /radiofrequency (CO2/RF), and the third received both treatments. Every patient received three treatment sessions one month apart. Patients were photographed, and a skin biopsy was taken from each area before and one month after treatment.Results: Assessment of the clinical photos showed that fractional CO2/radiofrequency gave a mild improvement in 22%, moderate improvement in 55.5% and marked improvement in 22.5%. Clinically, the combined treatment showed mild improvement in 44% of patients, moderate results in 33% and marked improvement in 23% of patients. The PRP as an only mode of treatment showed poor improvement in 22%, mild improvement in 23% and moderate improvement in 55% of patients. Biopsy results showed a decrease in collagen and elastin after treatment with the solitary methods, while the combined approach resulted in an increase in collagen and a reduction in elastin.Conclusion: Fractional CO2 laser/radiofrequency combined with PRP or either of them showed clinical improvement to variable degrees with superior results clinically and histologically with the combined method.Keywords: fractional CO2 laser radiofrequency, platelet rich plasma, PRP, striae distensae